Potential Impact of ALKBH5 and YTHDF1 on Tumor Immunity in Colon Adenocarcinoma - Yan, Guanyu; An, Yue; Xu, Boyang; Wang, Ningning; Sun, Xuren; Sun, Mingjun (Frontiers in Oncology, 2021)
Background ALKBH5 and YTHDF1 are regarded as the eraser and reader, respectively, in N6-methyladenosine (m6A) modification. Recently, immune contexture has been drawing increasing attention in terms of the progression and treatment of cancers. This study aimed to determine the relationship between ALKBH5/YTHDF1 and immunological characteristics of colon adenocarcinoma (COAD). Methods Expression of ALKBH5 and YTHDF1 was investigated across TCGA and GEO validated in our study. Patients with COAD were divided into two clusters using consensus clustering based on the expression of ALKBH5 and YTHDF1. We then compared their clinical characteristics and performed gene set enrichment analysis (GSEA) to identify the functional differences. Immune infiltration analyses were conducted using ESTIMATE, CIBERSORT, and ssGSEA. In addition, we evaluated the expression of the targets of immune checkpoint inhibitors (ICIs) and calculated the tumor mutation burden (TMB) of the tumor samples. Weighted gene co-expression network analysis (WGCNA) was used to identify the genes related to both ALKBH5/YTHDF1 expression and immunity. GSE39582 was utilized for external validation of immunological features between the two clusters. Results Cluster 2 had high expression of ALKBH5 and lesser so of YTHDF1, whereas Cluster 1 had just the reverse. Cluster 1 had a higher N stage and pathological stage than Cluster 2. The latter had stronger immune infiltration, higher expression of targets of ICIs, more TMB, and a larger proportion of deficiency in mismatch repair-microsatellite instability-high (dMMR-MSI-H) status than Cluster 1. Moreover, WGCNA revealed 14 genes, including PD1 and LAG3, related to both the expression of ALKBH5/YTHDF1 and immune scores. Conclusions ALKBH5 and YTHDF1 influence immune contexture and can potentially transform cold tumors into hot tumors in patients with COAD.